(3y+7)(-4x+2)=

Simple and best practice solution for (3y+7)(-4x+2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3y+7)(-4x+2)= equation:


Simplifying
(3y + 7)(-4x + 2) = 0

Reorder the terms:
(7 + 3y)(-4x + 2) = 0

Reorder the terms:
(7 + 3y)(2 + -4x) = 0

Multiply (7 + 3y) * (2 + -4x)
(7(2 + -4x) + 3y * (2 + -4x)) = 0
((2 * 7 + -4x * 7) + 3y * (2 + -4x)) = 0
((14 + -28x) + 3y * (2 + -4x)) = 0
(14 + -28x + (2 * 3y + -4x * 3y)) = 0

Reorder the terms:
(14 + -28x + (-12xy + 6y)) = 0
(14 + -28x + (-12xy + 6y)) = 0
(14 + -28x + -12xy + 6y) = 0

Solving
14 + -28x + -12xy + 6y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -28x + -12xy + -14 + 6y = 0 + -14

Reorder the terms:
14 + -14 + -28x + -12xy + 6y = 0 + -14

Combine like terms: 14 + -14 = 0
0 + -28x + -12xy + 6y = 0 + -14
-28x + -12xy + 6y = 0 + -14

Combine like terms: 0 + -14 = -14
-28x + -12xy + 6y = -14

Add '-6y' to each side of the equation.
-28x + -12xy + 6y + -6y = -14 + -6y

Combine like terms: 6y + -6y = 0
-28x + -12xy + 0 = -14 + -6y
-28x + -12xy = -14 + -6y

Reorder the terms:
14 + -28x + -12xy + 6y = -14 + -6y + 14 + 6y

Reorder the terms:
14 + -28x + -12xy + 6y = -14 + 14 + -6y + 6y

Combine like terms: -14 + 14 = 0
14 + -28x + -12xy + 6y = 0 + -6y + 6y
14 + -28x + -12xy + 6y = -6y + 6y

Combine like terms: -6y + 6y = 0
14 + -28x + -12xy + 6y = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(7 + -14x + -6xy + 3y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(7 + -14x + -6xy + 3y)' equal to zero and attempt to solve: Simplifying 7 + -14x + -6xy + 3y = 0 Solving 7 + -14x + -6xy + 3y = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -14x + -6xy + -7 + 3y = 0 + -7 Reorder the terms: 7 + -7 + -14x + -6xy + 3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -14x + -6xy + 3y = 0 + -7 -14x + -6xy + 3y = 0 + -7 Combine like terms: 0 + -7 = -7 -14x + -6xy + 3y = -7 Add '-3y' to each side of the equation. -14x + -6xy + 3y + -3y = -7 + -3y Combine like terms: 3y + -3y = 0 -14x + -6xy + 0 = -7 + -3y -14x + -6xy = -7 + -3y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| (6x^2+7)-(-4y^2+7)= | | 6x+15=64 | | sinx=73 | | (x+1)(10x)=(12x+2)x | | (6x+36)=(2x-5) | | 30=-3(-6-2z) | | -9x-22=-184 | | 6w^4+w^3-3w^2=0 | | 56+(7x-1)=90 | | (15/8)=((17-x)/x) | | 5n(4n+1)=0 | | 16+5a=31 | | 10x-6/3-5x | | 32-66= | | x-34=5x+2 | | (2x+6)+(5x+6)= | | 2x(-33)= | | 3a+3-4a+8=6 | | X^2+22x=-20 | | 9=5p+15-4p | | r^2-r=21+3r | | 3-36= | | 8z^4+8z^3=z+1 | | -2y+9(-2y+1)=-5+7(-8-y) | | 1,206.4/x=52 | | 325/26 | | x-12/x-10 | | Ln(x+5)-ln(x+4)=ln(x-1)-ln(x+2) | | H=-16t+200 | | 3y-5=-13+y | | 8k-15=-3k-59 | | (5x+40)(4x-2)=0 |

Equations solver categories